1867 Neb. Laws 68 - (:unkn) unknown (My University, 1867)
An Act to Incorporate Nebraska City, § 25: The city council shall regulate the keeping and sale of gun-powder within the city[.]
Keywords: GUNPOWDER - STORAGE